Real-Time Tracking Of Linac Parameters For Verification Of Dynamic Multileaf Collimator (DMLC) Based Radiotherapy Treatment - Midi, Nur Shaheera (2018)
Intensity Modulated Radiation Therapy (IMRT) delivers highly conformal dose to tumour using dynamic multileaf collimator (MLC). The complexity of IMRT delivery requires patient specific pre-treatment verification. This study investigates application of real-time tracking data for IMRT verification from two modern radiotherapy linacs of different tracking mechanism. Varian linac uses motor current feedback to track the MLC and logged the data as Varian log file (VLF), whereas Elekta linac uses optical tracking system and logged the data as Elekta log file (ELF).